A new fifth order implicit block method for solving first order stiff ordinary differential equations - Musa, Hamisu; Suleiman, Mohamed; Ismail, Fudziah; Senu, Norazak; Abdul Majid, Zanariah; Ibrahim, Zarina Bibi (Institute for Mathematical Research, Universiti Putra Malaysia, 2014)
A new implicit block backward differentiation formula that computes 3–points simultaneously is derived. The method is of order 5 and solves system of stiff ordinary differential equations (ODEs). The stability analysis indicates that the method is A–stable. Numerical results show that the method outperformed some existing block and non-block methodsfor solving stiff ODEs.